Prediction of epidemic peak and infected cases for COVID-19 disease in Malaysia, 2020 - Alsayed A.; Sadir H.; Kamil R.; Sari H. (MDPI AG, 2023)
COVID-19; disease control; epidemic; epidemiology; fuzzy mathematics; genetic algorithm; infectivity; mortality; prediction; viral disease; Article; calibration; coronavirus disease 2019; epidemic; forecasting; fuzzy system; genetic algorithm; human; Malaysia; model; mortality; prediction; uncertainty; validation process; Betacoronavirus; Coronavirus infection; health survey; pandemic; pathogenicity; public health service; quarantine; virus pneumonia; Malaysia; Coronavirus; Betacoronavirus; Coronavirus Infections; Forecasting; Health Surveys; Humans; Malaysia; Pandemics; Pneumonia, Viral; Public Health Administration; Quarantine